Updated S2K guidelines on the management of pemphigus vulgaris and foliaceus initiated by the european academy of dermatology and venereology (EADV). (24th August 2020) - Joly, P.; Horvath, B.; Patsatsi, Α; Uzun, S.; Bech, R.; Beissert, S.; Bergman, R.; Bernard, P.; Borradori, L.; Caproni, M.; Caux, F.; Cianchini, G.; et al.
Abstract: Background: Pemphigus encompasses a group of life‐threatening autoimmune bullous diseases characterized by blisters and erosions of the mucous membranes and skin. Before the era of immunosuppressive treatment, pemphigus was almost always fatal. Due to its rarity, only few randomized controlled therapeutic trials are available. Recently, rituximab has been approved as first‐line treatment for moderate and severe pemphigus vulgaris in Europe and the United States. Objectives: The Autoimmune blistering diseases Task Force of the European Academy of Dermatology and Venereology (EADV) has initiated a throughout update of the guideline for the management of patients with pemphigus. Results: The guidelines for the management of pemphigus were updated, and the degree of consent among all task force members was included. The final version of the guideline was consented by the European Dermatology Forum (EDF) and several patient organizations.